2010
DOI: 10.1144/sp347.7
|View full text |Cite
|
Sign up to set email alerts
|

Turbidite reservoir compartmentalization and well targeting with 4D seismic and production data: Schiehallion Field, UK

Abstract: This paper discusses integration of production surveillance techniques, focusing on the use of 4D seismic data to identify reservoir compartmentalization. We present two examples of recently drilled compartments that were successfully identified following integration of surveillance data with detailed reservoir modelling work. Our examples are from the faulted, Paleocene channelized turbidite reservoirs of the Schiehallion oil field, offshore West of Shetlands, U.K. The first example provides a good case histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
(16 reference statements)
2
15
0
Order By: Relevance
“…Some Paleogene oilfields in UK water have a complex architecture, formed by turbidite channels, sheet turbidite sandstones and sealing faults . Examples include the Schiehallion Field and Pierce Field (Gainski et al, 2010;Scott et al, 2010). In the Southern North Sea, it has been reported that the Triassic Bunter Sandstone aquifer is more suitable for CO2 storage reservoir than the Permian Rotliegend Sandstone because it has less compartmentalization problems (Holloway et al, 2006).…”
Section: The Geological Risks Of a Proven Reservoirmentioning
confidence: 99%
“…Some Paleogene oilfields in UK water have a complex architecture, formed by turbidite channels, sheet turbidite sandstones and sealing faults . Examples include the Schiehallion Field and Pierce Field (Gainski et al, 2010;Scott et al, 2010). In the Southern North Sea, it has been reported that the Triassic Bunter Sandstone aquifer is more suitable for CO2 storage reservoir than the Permian Rotliegend Sandstone because it has less compartmentalization problems (Holloway et al, 2006).…”
Section: The Geological Risks Of a Proven Reservoirmentioning
confidence: 99%
“…This leaves the middle and western regions devoid of well control. The area coloured yellow represent volume of gas not tested by any well often realized through experience relatively late in production life of reservoirs (Gainski et al 2010). Successful field appraisal and production optimization can be achieved through accurate characterization and prediction of reservoir compartmentalization and its effects on fluid flow (Barkved et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These bodies are composed of heterogeneous deposits that can contain fluids or act as flow barriers. Such barriers may compartmentalize the reservoir and make its exploitation harder, especially when combined with sealing faults [e.g., Gainski et al, 2010]. Channel modeling can help to study and anticipate more precisely the flow behavior.…”
mentioning
confidence: 99%